Collaborative coding in assembly language - Mansor, Hafizah (2024)
Assembly Language is a low-level programming language - closely tied to hardware, typically used for performance-critical applications. It can be challenging for students who are accustomed to and familiar with high-level languages, where the hardware details are abstracted away. Hence, a different approach is used to enhance the learning experience in the CSCI 3301 (Computer Architecture and Assembly Language) course. One of the assessments includes a Group Project, which accounts for 25% of the overall grade. In the group project, students are given 3-4 options of titles to work on. The titles are impactful real-world IoT applications. Through this activity, students can learn assembly language programming (using the MIPS ISA and MARS simulator) and at the same time design and develop impactful solutions.